Titanium vs. polyetheretherketone (PEEK) interbody fusion: Meta-analysis and review of the literature - Seaman, Scott; Kerezoudis, Panagiotis; Bydon, Mohamad; Torner, James C.; Hitchon, Patrick W. (Journal of clinical neuroscience, 2017)
•Current literature suggests comparable Ti and PEEK cage spinal fusion rates.•Of the 2 cage materials, Ti is associated with increased subsidence.•Prospective studies should identify the benefits of one material over the other. Spinal interbody fusion is a standard and accepted method for spinal fusion. Interbody fusion devices include titanium (Ti) and polyetheretherketone (PEEK) cages with distinct biomechanical properties. Titanium and PEEK cages have been evaluated in the cervical and lumbar spine, with conflicting results in bony fusion and subsidence. Using Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) guidelines, we reviewed the available literature evaluating Ti and PEEK cages to assess subsidence and fusion rates. Six studies were included in the analysis, 3 of which were class IV evidence, 2 were class III, and 1 was class II. A total of 410 patients (Ti-228, PEEK-182) and 587 levels (Ti-327, PEEK-260) were studied. Pooled mean age was 50.8years in the Ti group, and 53.1years in the PEEK group. Anterior cervical discectomy was performed in 4 studies (395 levels) and transforaminal interbody fusion in 2 studies (192 levels). No statistically significant difference was found between groups with fusion (OR 1.16, 95% C.I 0.59–2.89, p=0.686, I2=49.7%) but there was a statistically significant the rate of subsidence with titanium (OR 3.59, 95% C.I 1.28–10.07, p=0.015, I2=56.9%) at last follow-up. Titanium and PEEK cages are associated with a similar rate of fusion, but there is an increased rate of subsidence with titanium cage. Future prospective randomized controlled trials are needed to further evaluate these cages using surgical and patient-reported outcomes.